VARIOUS DIMENSIONS OF COMMUNICATION IN SHRI RAMCHARITMANAS - Singh, Mahendra Pratap; Kumar, Umesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Communication is the basis of progress of human society. Communication plays an important role in the non-human world as well. Communication is the means of many activities taking place in humans and other living beings. Developed life forms cannot be imagined without communication. Many forms of human communication have been described in communication science. Since ancient times, Indian sages, scholars and literary creators have pondered over all these forms of communication and have used them in various works. Shri Ramcharitmanas is one such epic, in whose expression Tulsidas ji has not only used these forms of communication, but has also given space to new experiments. In this research article, various forms and dimensions of communication described in Shri Ramcharitmanas have been studied. Keeping in view the word limit of the research article, verbal-nonverbal communication, symbolic communication, intrapersonal communication, interpersonal communication, group communication, mass communication and communication from non-human nature have been made the basis.